Sourcing ideas - Steed, Josephine; Stevenson, Frances (Lausanne : AVA Academia, 2012)
'Basics Textile Design' titles provide visual arts students with a theoretical and practical exploration of each of the fundamental topics within the discipline of textile design.
What is textile design? : What does a textile designer do? ; What are the occupations? ; Case study : Reiko Sudo ; Interview : Donna Wilson -- Research for textiles : What do designers research? ; What is primary research? ; What is secondary research? ; Case study : Becky Earley ; Interview : J.R. Campbell -- The toolkit : Tools for primary research ; Tools for secondary research ; Case study : Maggie Orth ; Interview : Linda Florence -- Planning research : Design briefs ; Generating a theme ; Methods to explore the theme ; Case study : Manish Arora ; Interview : Johanna Basford -- Observation and analysis : Colour ; Surface ; Structure ; Texture ; Pattern ; Case study : Yinka Shonibare ; Interview : Tim Gresham -- Techniques for observational drawing : Drawing techniques ; Mixed media ; Scale and dimensions ; Case study : Missoni ; Interview : James Donald -- Appendix : How to present your research : Visual presentation ; CAD presentation ; Verbal presentation -- Conclusion -- Glossary.
Includes bibliographical references and index.
Keywords: Textile design; Textile design -- Case studies; Textile designers -- Interviews; Textile design -- Research; Textile industry